The Role of FeNO in Predicting Asthma - Pijnenburg, Mariëlle W. (Frontiers in Pediatrics, 2019)
Asthma-like symptoms like wheezing and dyspnea affect 1in every 3 preschool children. An easily available biomarker that predicts later asthma or unfavorable lung growth in these children may be helpful in targeting the right child with the right drugs and avoiding exposure to potentially harmful drugs in others. The fraction of exhaled nitric oxide (FeNO) has been suggested as a marker of eosinophilic inflammation. FeNO can be measured in a standardized way from the age of 4 but several methods have been developed to measure FeNO also in younger children. Several studies have assessed the predictive value of FeNO in preschool wheezing children for asthma later in life. These studies have shown that FeNO may be helpful in defining different preschool wheezing phenotypes, and in assessing the risk of later asthma or impaired lung growth. However, data are conflicting on the added value over clinical parameters. In two studies in school children, high FeNO was predictive for asthma development during follow up and also predicted lower lung function growth. In school children with respiratory symptoms suggestive of asthma, particularly in atopic children, FeNO has diagnostic value for an asthma diagnosis, mostly for ruling in asthma. There are not enough data to assess if FeNO has a predictive value for lung development in school children.